Loss of fructose-1,6-bisphosphatase induces glycolysis and promotes apoptosis resistance of cancer stem-like cells: an important role in hexavalent chromium-induced carcinogenesis - Dai, Jin (Toxicol Appl Pharmacol, 2017)
Hexavalent chromium (Cr(VI)) compounds are confirmed human carcinogens for lung cancer. Our previous studies has demonstrated that chronic exposure of human bronchial epithelial BEAS-2B cells to low dose of Cr(VI) causes malignant cell transformation. The acquisition of cancer stem cell-like properties is involved in the initiation of cancers. The present study has observed that a small population of cancer stem-like cells (BEAS-2B-Cr-CSC) exists in the Cr(VI)-transformed cells (BEAS-2B-Cr). Those BEAS-2B-Cr-CSC exhibit extremely reduced capability of generating reactive oxygen species (ROS) and apoptosis resistance. BEAS-2B-Cr-CSC are metabolic inactive as evidenced by reductions in oxygen consumption, glucose uptake, ATP production, and lactate production. Most importantly, BEAS-2B-Cr-CSC are more tumorigenic with high levels of cell self-renewal genes, Notch1 and p21. Further study has found that fructose-1,6-bisphosphatase (FBP1), an rate-limiting enzyme driving glyconeogenesis, was lost in BEAS-2B-Cr-CSC. Forced expression of FBP1 in BEAS-2B-Cr-CSC restored ROS generation, resulting in increased apoptosis, leading to inhibition of tumorigenesis. In summary, the present study suggests that loss of FBP1 is a critical event in tumorigenesis of Cr(VI)-transformed cells.